INVESTIGATION OF THE ACTIVITY AND PATHOGENECITY OF STAPHYLOCOCCUS AUREUS ENTEROTOXIN C BY LIGATED ILEAL LOOP ASSAY IN RABBITS - Basil A. Abbas Mohammed H. Khudor Hasan I. Idbeis (Basrah Journal of Veterinary Research)
Three enterotoxigenic isolates of Staphylococcus aureus previously isolated from contaminated milk and evaluated for their enterotoxin producing ability and histopathological changes by the ligated rabbit ileal loop assay. The results of this assay revealed that crud toxin obtained by these isolates caused fluid accumulation in rabbit ileal loops. Fluid aspirated from the loops was bloody and the histopathological changes in sections were characterized by moderate to sever haemorrhage, erosion and inflammatory cells, in addition there was distortion and shift of villi. This finding established that staphylococcal enterotoxin that associated with vomiting and diarrhea , which often abate within 24 hrs., there was potential risk for more serious disturbances such as inflammation, tissue damage and toxic shock.